Calvin's New Testament commentaries ; vol. 10 - Calvin, John, 1509-1564; Smail, T.A..; Torrance, David W.; Torrance, Thomas Forsyth, 1913- (Grand Rapids, MI Eerdmans, 1964)
Contents : v. 10 : The Second epistle of Paul the Apostle to the Corinthians and the epistles to Timothy, Titus and Philemon. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Corinthians, 2nd -- commentaries; Bible. N.T. Timothy -- commentaries; Bible. N.T. Titus -- commentaries; Bible. N.T. Philemon -- commentaries